Contemporary Poetry. (Edinburgh critical guides to literature., 2011)
Discussing the work of more than 60 poets from the US, UK, Ireland, Australia, New Zealand and the Caribbean, Nerys Williams guides students through the key ideas and movements in the study of poetry today.